Cochrane Database of Systematic Reviews 2009
DOI: 10.1002/14651858.cd006589.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Oral iron supplementation for preventing or treating anaemia among children in malaria-endemic areas

Abstract: Iron does not increase the risk of clinical malaria or death, when regular malaria surveillance and treatment services are provided. There is no need to screen for anaemia prior to iron supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 191 publications
2
69
0
1
Order By: Relevance
“…49 Screening for iron deficiency in resource-limited areas is indeed challenging, controversial, and may neither be needed nor practical. 44,[49][50][51] In a hyperendemic malaria region of Tanzania, over 800 infants were randomized to one of four groups-iron supplementation with anti-malarial, iron supplementation with placebo, placebo with anti-malarial, or placebo with placebo. Infants receiving iron had lower rates of severe anemia than their counterparts without an effect on acquisition of malaria, suggesting the protective efficacy of iron supplementation in preventing anemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…49 Screening for iron deficiency in resource-limited areas is indeed challenging, controversial, and may neither be needed nor practical. 44,[49][50][51] In a hyperendemic malaria region of Tanzania, over 800 infants were randomized to one of four groups-iron supplementation with anti-malarial, iron supplementation with placebo, placebo with anti-malarial, or placebo with placebo. Infants receiving iron had lower rates of severe anemia than their counterparts without an effect on acquisition of malaria, suggesting the protective efficacy of iron supplementation in preventing anemia.…”
Section: Discussionmentioning
confidence: 99%
“…53 A Cochrane review in 2009, which reviewed 68 trials (and over 40,000 children) concluded that iron supplementation did not increase the risk of malaria, unless malaria surveillance and treatment options were not provided to infected children. 50 Consequently, these researchers note that screening for IDA is not necessary in areas where malaria surveillance, prevention, and treatment programs are implemented. A subsequent Cochrane review in 2011 confirmed the earlier findings and found that while the risk of clinical malaria among children receiving iron supplementation was higher in regions without access to malaria surveillance and treatment, concluded that "when regular malaria surveillance and treatment services are provided" the risk of malaria is not increased.…”
Section: Discussionmentioning
confidence: 99%
“…However, prospective controlled human studies on the interaction between iron status and malaria have not yet been performed, but a Cochrane review on oral iron supplementation for anemia in children in malaria-endemic areas did not demonstrate any significant change in the prevalence of malaria in iron supplemented children [31].…”
Section: Iron Fortification Of Foodsmentioning
confidence: 99%
“…Of those, seven contained mortality data from at least five studies and were included. The interventions were oral iron supplementation for anemia, 13 rotavirus vaccination, 14 vitamin A supplementation, 10 chemoprophylaxis for malaria, 15 injected cholera vaccination, 16 insecticide-treated bed nets, 17 and pneumococcal conjugate vaccines. 18 Results from the meta-analyses are shown in Figure 1B.…”
Section: Resultsmentioning
confidence: 99%